Analysis of Abstinence to Eat and Vulva Hygiene Behavior on Healing Perineal Wounds in Postpartum Mothers on Day 7 at Bpm Ny J Puspo Pasuruan Village - Rizkika Wijayanti; Candra Wahyuni (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2023)
Perineal tears occur in almost all normal birth processes and not infrequently perineal tears can result in perineal infections, causing a long wound healing process. This occurs because some postpartum mothers experience abstinence from food and lack of vulva hygiene behavior. The purpose of this study was to determine the relationship between abstinence from food and vulva hygiene behavior on perineal wound healing on the 7th day of postpartum mother at Bpm Ny. J Puspo Village. This study is a correlational study using questionnaires and observation instruments. The population is all postpartum women with perineal wounds. This study uses the Pearson test. The results of the study found that as many as (25.7%) of respondents had the habit of abstaining from food and (42.5%) did not perform vulva hygiene, found as many as (37.1%) of respondents who had old perineal wound healing. While the behavior of Vulva Hygiene test results with correlation coefficient analysis r 0.616 > r table (0.3338) then there is a significant relationship then seen from Sig = 0.000 which means Sig 0.000 <0.05 then there is a relationship so that Ho is rejected Ha is accepted meaning there is a relationship abstinence from eating with perineal wound healing. With the analysis of the correlation coefficient, the value of r is 0.606 > r table (0.3338) so there is a significant relationship (Ha is accepted), then seen from Sig = 0.000 which means Sig 0.000 <0.05 then there is a relationship so that Ho is rejected Ha is accepted This means that there is a relationship between vulva hygiene behavior and perineal wound healing. There is a relationship between abstinence from eating and vulva hygiene behavior towards perineal wound healing on the 7th day of postpartum women. It is hoped that health workers will increase patient education about vulva hygiene behavior and avoid abstinence from eating habits for perineal wound healing.